Exploring the experiences of resident doctors in child and adolescent psychiatry with virtual reality-based simulation training: a qualitative study - Siv Lena Birkheim; Giovanna Calogiuri; Mette Hvalstad; Randi Martinsen (BMC, 2024)
Abstract Background The use of virtual reality simulation for the training of non-technical skills among healthcare professionals may improve professional development as well as the quality of care. This study aims to explore the experiences of resident doctors in child and adolescent psychiatry with the use of virtual reality-based simulation for the training of non-technical skills. Methods The study had an exploratory qualitative design. Data were collected through observations of thirteen resident doctors in child and adolescent psychiatry during their participation in three virtual reality-based simulation sessions, followed by two focus groups. Data were analyzed using reflective thematic analysis. Results The analysis revealed the following three themes: 1) The importance of pedagogical principles, 2) Playful and motionally affected learning, and 3) Observational learning contributing to lifelong learning. Conclusions Virtual reality-based simulation was felt to be an appropriate method of training non-technical skills for resident doctors in child and adolescent psychiatry. In particular, the intervention met resident doctors' desires and needs regarding learning through observation and peer discussions. However, some challenges related to technical issues and the content of the scenarios were highlighted. This method may not only increase the resident doctors' self-efficacy and competence, but also contribute to their lifelong learning.